Implementing the Panel Event Study - Damian Clarke; Kathya Tapia Schythe (Institute of Labor Economics (IZA), 2020)
Many studies estimate the impact of exposure to some quasi-experimental policy or event using a panel event study design. These models, as a generalized extension of 'difference-in-differences' or two-way fixed effect models, allow for dynamic lags and leads to the event of interest to be estimated, while also controlling for fixed factors (often) by area and time. In this paper we discuss the set-up of the panel event study design in a range of situations, and lay out a number of practical considerations for its estimation. We describe a Stata command eventdd that allows for simple estimation, inference, and visualization of event study models in a range of circumstances. We then provide a number of examples to illustrate eventdd's use and flexibility, as well as its interaction with various native Stata routines, and other relevant user-written libraries such as reghdfe and boottest.
Keywords: C1; C13; C51; C54; C63; C87; 330; event studies; difference-in-differences; estimation; inference; visualization